Youth Activists and Democracy : A Literature Review of Contributions to the Transformation of Critical Citizenship - Pinandhita, Peni; Rafa; Salsabila, Lubna; Susalti Nur Arsyad (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2025)
Effective political socialization fosters strong political awareness, which in turn encourages active and meaningful political participation. A critical citizen not only understands their rights and responsibilities but also possesses the ability to think reflectively and respond to social injustices. To strengthen political awareness among the younger generation, it is necessary to have political socialization agents who can tailor their strategies to the characteristics of youth. In this study, the agent in question is young activists. The method employed in this research is a literature study. The findings indicate that young activists play a significant role in enhancing political awareness among the younger generation and in shaping the character of critical citizens. Although often perceived as lacking experience, young activists have demonstrated a tangible impact in cultivating critical citizenship through various initiatives. This study aims to examine the contribution of young activists as political socialization agents in shaping critical citizens. The findings show that young activists have successfully acted as political socialization agents who strengthen political awareness among youth.